2015
DOI: 10.1007/s10961-015-9429-4
|View full text |Cite
|
Sign up to set email alerts
|

Scientific research groups’ cooperation with firms and government agencies: motivations and barriers

Abstract: The behavior of academic researchers who engage in cooperation with industrial partners has already been the subject of considerable research. A lack of understanding exists regarding the motivations of scientific research groups to engage in cooperation with other types of external non-academic organizations and the perceived barriers that may inhibit this activity. In this paper we analyse the motivations and perceptions of risks that shape scientific research groups' cooperation with industry and government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 56 publications
3
50
0
4
Order By: Relevance
“…A number of studies have thus considered a broader set of KT activities, focusing on academics' propensity to undertake them (Ramos-Vielba et al, 2016;Olmos-Peñuela et al, 2014;D'Este and Perkmann, 2011;Landry et al, 2010;Grimpe and Fier, 2010;D'Este and Patel, 2007;Link et al, 2007) and their relative effects (Landry et al, 2007;D'Este et al, 2013;Sánchez-Barrioluengo, 2014). For example, D' Este and Patel (2007) are among the first to include contract research and consulting activity in the analysis of KT activities.…”
Section: Variety and Intensity Of Knowledge Transfer Activities: A Tamentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have thus considered a broader set of KT activities, focusing on academics' propensity to undertake them (Ramos-Vielba et al, 2016;Olmos-Peñuela et al, 2014;D'Este and Perkmann, 2011;Landry et al, 2010;Grimpe and Fier, 2010;D'Este and Patel, 2007;Link et al, 2007) and their relative effects (Landry et al, 2007;D'Este et al, 2013;Sánchez-Barrioluengo, 2014). For example, D' Este and Patel (2007) are among the first to include contract research and consulting activity in the analysis of KT activities.…”
Section: Variety and Intensity Of Knowledge Transfer Activities: A Tamentioning
confidence: 99%
“…Only recently have a number of contributions considered a broader set of KT activities and focused on the motivation of academics to perform these activities (Ramos-Vielba et al, 2016;Olmos-Peñuela et al, 2014;D'Este and Perkmann, 2011;D'Este and Patel, 2007;Link et al, 2007), their complementarities (Landry et al, 2010) and their effects on effective KT (Landry et al, 2007). This stream of literature has shown that academic engagement is mainly influenced by individual characteristics (Link and Scott, 2012), organisational and institutional factors (Moog et al, 2015;Ding and Choi, 2011;Jensen and Thursby, 2001), the scientific discipline of the academic (Bekkers and Bodas Freitas, 2008) and a combination of intrinsic and extrinsic motivations: fundraising, access to knowledge and learning (D'Este and Perkmann, 2011;Lam, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…RG are responsible for promoting relations between education, research and extension (Backes, Prado, Lino, Ferraz, Reibnitz, & Canever, 2012;Riquelme & Langer, 2010), considering the needs of funding agencies (Pereira & Andrade, 2008) and the practical use of theoretical knowledge (Araujo, Mascarini, Santos, & Costa, 2015;Caliari, Santos, & Mendes, 2016;Ramos-Vielba, Sánchez-Barrioluengo, & Woolley, 2016;Riquelme & Langer, 2010).…”
Section: Results In Research Groupsmentioning
confidence: 99%
“…The same occurred when the group developed software for its peers (presumably because receiving a new product is not necessarily creating new technology), regarding technical consultancy activities (it may represent a specialised service but not necessarily a relationship between science and technology) or when the peer supplied materials and inputs for the group (it may represent a business relationship, not a scientific and technological one). Ramos-Vielba et al (2016) studied motivation and obstacles to cooperation between scientific investigation groups, companies and government agencies in Spain addressing characteristics of the research group; relations between the group and other agents in the innovation system; cooperation with companies; and the regional context for intersectoral cooperation with non-academic organizations. The findings indicated that most RG cooperate with both companies and government.…”
Section: Results In Research Groupsmentioning
confidence: 99%
See 1 more Smart Citation